Corona in the Arabic novel between reality and imagination, a balancing study between thenovels «Khafafich Corona» by Ibrahim Rasoul and " Freedom in the Time of Corona" bySundus Al-Shawi. (مجلة إحالات, 2026)
The world has recently witnessed stagnation in various fields and domains due to the Coronapandemic, which has become the dilemma of the century, and despite the severe humanitarian disasters caused by the latter, at the same time it opened wide horizons and formed a fertile ground in which creators dive in to extract creative works of literary art from them. Distinctive, and in this context specifically, myintervention, tagged “Corona” in the Arabic novel between reality and the imaginary, came as a balancing study between the two novels “Corona Bats” by Ibrahim Rasool and “Freedom in the Time of Corona” by Sondos Al-Shawi. , through which I seek to shed light on the manifestations of this pandemic in the literarycreativity of the Arab novelist, and to know how Corona was manifested in the two novels? How did thewriters deal with it based on the two novels? What are the connotations that the topic of Corona carriedwithin the two novels?